THE EFFECT OF VALUE-ORIENTED ACTIVITIES ON APPROACHING SOCIAL PROBLEMS DUE TO TECHNOLOGY - BAYRAK, Beyhan; AKDEMİR , Abamüslim (SSD Journal, 2022)
This study, it is aimed to determine the effect of value-oriented activities on the comprehension of technology based social problems within the scope of social studies courses. In the research, a mixed method, in which qualitative and quantitative methods are used together, was preferred. In the quantitative dimension of the study, a quasi-experimental design with pretest-posttest control group was used. Data collection tools were prepared in accordance with the qualitative method. The study group of the research consists of a total of 96 students attending the seventh grade in a state secondary school in the Gemlik district of Bursa in the 2019-2020 academic year. The research was carried out with two experimental groups (n=47) and two control groups (n=49). Value-oriented activities prepared for the teaching of technology-based social problems were applied to the experimental group students for 6 lesson hours. In this process, no intervention was made for the education of the control group. In the research, "Social Problems Questionnaire", "Problem Tree Diagram" and "Social Change and Values Questionnaire", which are data collection tools, were made by the students in the experimental group and control group before and after the application. The obtained data were subjected to content analysis. As a result of the analyzes made on the causes of technology-related social problems, their effects on society, their solutions and their relationship with values, it was seen that while the expressions of the experimental group and control group students were similar before the application, the expressions of the experimental group students after the application were considerably enriched and diversified compared to the expressions of the control group students. In addition, while there was a significant difference in the percentages of change in the expressions of the students in the experimental group before and after the application, it was determined that this difference was not significant in the control group.